2014
DOI: 10.4028/www.scientific.net/amm.535.683
|View full text |Cite
|
Sign up to set email alerts
|

Development of Catalyst for Industrial Flue Gas Denitration at Low Temperature

Abstract: The most effective technology currently for flue gas denitrition is selective catalytic reduction (SCR). And the major problem against spreading SCR technology is the high cost and low efficiency of the catalyst for SCR. Al2O3 supported Mn-Fe oxide precursor was prepared through water/ethanol coprecipitation and then nitridized through NH3-TPD. Thus the inexpensive and efficient Mn-Fe-O-N/Al2O3 catalyst was obtained. The catalyst with a Mn/Al molar ratio of 0.4 and a Fe loading of 6.0 wt.% was testified to hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…Furthermore, the introduction of Mo also reduced the deactivation of the catalyst and increased the effective temperature range of SCR reaction. Yang et al89 indicated that the conversion of NO on the Fe-Mn/Al 2 O 3 catalyst exceeded 95% at 150-200 1C. It was concluded that the doping of Fe accelerated the electron transfer between Mn n+ and Fe n+ at different valence states and enhanced the synergistic effect between the active component MnO x and the carrier Al 2 O 3 , which improved the redox performance and surface acidity of the catalyst.…”
mentioning
confidence: 99%
“…Furthermore, the introduction of Mo also reduced the deactivation of the catalyst and increased the effective temperature range of SCR reaction. Yang et al89 indicated that the conversion of NO on the Fe-Mn/Al 2 O 3 catalyst exceeded 95% at 150-200 1C. It was concluded that the doping of Fe accelerated the electron transfer between Mn n+ and Fe n+ at different valence states and enhanced the synergistic effect between the active component MnO x and the carrier Al 2 O 3 , which improved the redox performance and surface acidity of the catalyst.…”
mentioning
confidence: 99%